2015
DOI: 10.1108/lhs-11-2014-0076
|View full text |Cite
|
Sign up to set email alerts
|

Employee perceptions of managers’ leadership over time

Abstract: The present findings contribute to a deeper empirical understanding of leadership as it is practised over time in everyday contexts among employees in healthcare organisations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Notably the increase in confidence precedes the change of overt behaviours; this can be in line with findings by Chan and Drasgow (2001), where an increase in confidence gives rise to further willingness and openness to training, as well as openness to continual development of leadership. The result is also in line with the research of Palm et al (2015) showing the positive outcomes for the employees when the self-confidence of the leader increased.…”
Section: Discussionsupporting
confidence: 90%
“…Notably the increase in confidence precedes the change of overt behaviours; this can be in line with findings by Chan and Drasgow (2001), where an increase in confidence gives rise to further willingness and openness to training, as well as openness to continual development of leadership. The result is also in line with the research of Palm et al (2015) showing the positive outcomes for the employees when the self-confidence of the leader increased.…”
Section: Discussionsupporting
confidence: 90%
“…The ability of a leader to provide followers with tools for reducing their level of anxiety (related to change) and provide them with psychological safety is an additional factor that can have an effect upon followers’ assessments of leadership (Shamir, 2007). A study of employees whose managers had participated in a two-year employer leadership development programme reported that informants viewed their managers’ leadership as having changed in this period and that these changes were described as being positive (Avolio and Bass, 1998; Day, 2001; Dvir et al , 2002; Palm et al , 2015).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Therefore, the years of employment of leaders in an organization does not automatically bring about an instantaneous transformation in the organizational context. On the other hand, Palm et al refute the latter in concluding that transformation of the leaders can happen over time [21]. Kotur and Anbazhagan mentioned that there is a transition from one leadership style to another style with experience [22].…”
Section: Discussionmentioning
confidence: 99%